EFL Students' Perceptions and Experiences on English Online Learning During Covid-19 Pandemic in A Vocational High School - Susanti, Rasusi; Danugiri, Dadang; Pahlevi, Muhammad Reza (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2022)
The COVID-19 pandemic cannot be avoided at this time. Various policy changes began to be implemented, one of which was the online learning policy in all educational institutions, and one of them was the Vocational High School (SMK). During online learning, various kinds of obstacles arise, and of course, it is felt by vocational students. These obstacles give rise to various views of vocational students. Therefore, this study aimed to determine the perceptions of vocational students during online EFL classes. This study focused on six students of class XII Office Administration who participated in the study. This study uses a narrative inquiry research design. Data were collected through observation, semi-structured interviews, and documentation. Observations were made during four meetings in learning through Google Meet calls. Interviews were conducted via Google Meet calls. And documentation in the form of photos of students in online learning activities. This research uses thematic analysis by Braun and Clark (2006), which includes six steps to analyze the data. The results of the study found that learning English online for vocational students had many obstacles. These obstacles include the lack of teachers using different media when doing online learning, being too fast and lacking in detail in delivering knowledge, students being lazy to learn because they are too dependent on translator applications, and problems with the students' or teachers' internet connections. However, there are advantages to online learning. The advantage is that they feel more courageous in expressing their opinions in the ongoing learning activities.